Relating a Gluon Mass Scale to an Infrared Fixed Point in Pure Gauge QCD - Aguilar, A. C. [UNESP]; Natale, A. A. [UNESP]; da Silva, P. S. Rodrigues [UNESP] (American Physical Society (APS), 2003)
We show that in pure gauge QCD (or any pure non-Abelian gauge theory) the condition for the existence of a global minimum of energy with a gluon (gauge boson) mass scale also implies the existence of a fixed point of the [Formula presented] function. We argue that the frozen value of the coupling constant found in some solutions of the Schwinger-Dyson equations of QCD can be related to this fixed point. We also discuss how the inclusion of fermions modifies this property. © 2003 The American Physical Society.